Higher School Teachers Training Model Features - Drovnikov, Aleksander S.; Vazieva, Alfiya R.; Khakimova, Nailya G.; Konyushenko, Svetlana M.; Valeyev, Azat S.; Maksimova, Elvira V.; Ishmuradova, Alfiya M.; Khairullina, Elmira R. (International Review of Management and Marketing, 2016)
The formation of a new generation of experts depends on their scientific qualification, professional and pedagogical competence. In this regard, this article aims to identify the peculiarities of their training in the system training. The leading method in the study of this problem is the method of modeling, which allows to represent the process of higher school teachers’ advanced training as a whole system of components (theoretical, content, technology, assessment), the integrity of which is aimed at improving their research, self-education, organizational competencies. The requirements to the content of the teachers’ training in the process of their qualifications’ improving are revealed, goals and objectives are defined, the principles of this process are formulated, technological and scientific-methodical support of the process is developed; the features of quality’s control monitoring of teachers ’ professional development are revealed in the article. The article is valuable for leaders and teachers of the system of additional professional education. Keywords: Professional Development, Management of Education, Higher School Teachers, Additional Professional Education. JEL Classifications: A23, I23, I26